Qualitative Analysis of Problems Faced by Indonesian Students in Translation Subject - Muh Anwar; Nurming Saleh; Wahyu Kurniati Asri; Ambo Dalle; Hasmawati Hasmawati (Makassar State University, 2020)
The purpose of this study was to investigate problems faced by Indonesian students in learning German translation subject. This study uses a qualitative approach with the aim of discovering the problems experienced by students in-depth during the translation course. Data collection techniques used were interviews and observation. The research respondents were students majoring in German language education who were programming courses in translation. After the data is collected, the data is analyzed descriptively qualitatively. Data that has been analyzed are then verified again by conducting Focus Group Discussion (FGD) to several students. The purpose of this FGD is to check the data collected. Finding shows that there are several difficulties or problems faced by students during their translation courses, both related to the lack of vocabulary, the lack of mastery of source language culture, and the low understanding of translation material. However, the most fundamental problem is the lack of mastery of the source language culture